Is China a winner of the Russia-Ukraine war? - Gao, Boyang; Adnan, Zatul Himmah; Lee, Yok Fee; Wan Mohd Nor, Murni (Faculty of Human Ecology, Universiti Putra Malaysia, 2023)
China's action towards the Russia-Ukraine war was perceived as an ally rather than in a neutral position. However, what could China gain from the war? This paper discusses the argument by answering the following questions: What goals and foreign policy values China showed through its actions during the Russia-Ukraine war? Whether China’s foreign policy values demonstrated during the war help China to achieve its goals? Based on the document review, the paper seeks to identify the goals and foreign policy values adopted by China through her actions during the war. The paper finds that the actions of China during the war mainly aimed to challenge the Western-dominated international order and enhance the CPC’s domestic rule. China’s behaviours during the war showed several conflicting values. This paper suggested that this will negatively and significantly impact China’s foreign policy. As a result, China's attempt to challenge the Western-dominated international order might be failed. Also, China’s value portrayed in this war can only temporarily solidify the CPC’s regime.